Antimicrobial efficacy of fruit extracts of two Piper species against selected bacterial and oral fungal pathogens - Kamal Rai Aneja; Radhika Joshi; Chetan Sharma; Ashish Aneja (Universidade Estadual de Campinas, 2015)
Aim: To assess the antimicrobial efficacy of five solvent extracts of two Piper species commonly used in diet and traditional medicine, P. cubeba and P. longum, against selected bacterial and oral fungal pathogens i.e. Streptococcus mutans, Staphylococcus aureus, Candida albicans and Saccharomyces cerevisiae. Methods: The antimicrobial activity of five extracts of cubeb berries and Indian long pepper fruits was determined by the agar well diffusion method. The minimum inhibitory concentration (MIC) for the acetonic, methanolic and ethanolic extracts was determined by the modified agar well diffusion method. Results: Of the 5 fruit extracts evaluated, acetone, ethanol and methanol extracts of both the Piper spp. were found to have variable antimicrobial activities against all the four oral pathogens. The acetonic fruit extract of P. cubeba was the most effective against both the yeasts with the highest zone of inhibition (15.31 mm) against C. albicans followed by the methanolic (12.31 mm) and ethanolic (11.94 mm) extracts. C. albicans was found to be most sensitive pathogen, which survived up to 6.25 mg/mL in the acetonic extract (MIC = 12.5 mg/mL) followed by the methanolic and ethanolic extracts (MIC = 25 mg/mL). The acetonic, methanolic and ethanolic extracts of P. longum fruits showed almost equal inhibition zones of both yeasts, ranging between 10.64 and 14 mm. C. albicans survived up to 12.5 mg/mL (MIC= 25 mg/mL) while S.cerevisiae survived up to 25 mg/mL (MIC = 50 mg/mL). Conclusions: The crude extracts obtained from the fruits of the two Piper spp. may be used to treat oral fungal species, especially C. albicans, as they produced larger inhibition zones than antifungal drugs often used to treat these pathogens.